Apolipoproteins in ischemic stroke progression and recovery: Key molecular mechanisms and therapeutic potential - Tamara Etuze; Hortense Triniac; Ze Zheng; Denis Vivien; Fatemeh Dubois (Neurobiology of Disease)
Ischemic stroke, responsible for 80 % of all strokes, is a leading cause of mortality globally. While altered lipids profiles are recognized as modifiable risk factors, their direct impact on stroke outcomes is less understood due to the brain's distinct lipid metabolism and the selective permeability of the blood-brain barrier for lipoproteins. As key components of lipoproteins, apolipoproteins are essential for lipid transport, redistribution and metabolism in both the central nervous system and peripheral blood circulation. This review provides an updated perspective on the influence of brain-expressed apolipoproteins (such as ApoE, ApoA-I, ApoJ, ApoD, and others) and those that cross the damaged blood-brain barrier following ischemic stroke. We explore hypotheses regarding their involvement in molecular pathways related to lipid metabolism, inflammation, oxidative stress, mitochondrial function and blood-brain barrier integrity. Through this synthesis, we aim to identify potential biomarkers and therapeutic targets, thereby enhancing our understanding of apolipoproteins in ischemic stroke progression and contributing to improved clinical outcomes.